Physiochemical and in vitro cytotoxicity properties of biocompatible palm fatty acid-based polyesters - Tze, Yvonne Qzian Ling; Yiing, Jye Yap; Yi, Xin Heng; Siang, Yin Lee; Rhun, Yian Koh; Teck, Desmond Chye Ang; Chin, Hua Chia; Seng, Neon Gan (Penerbit Universiti Kebangsaan Malaysia, 2021)
With the sharp rise in global interest in sustainability and environmental concerns, there is a growing demand in replacing petroleum-derived raw materials with renewable plant-based raw materials in the production of polymers. In this study, two palm fatty acid polyesters were synthesized from palmitic and stearic acids. Their chemical structures were identified by FTIR and 1H-NMR analysis. Both polyesters showed a moderately high conversion rate from the acid value determination. DSC analysis showed that the palmitic acid polyester (PAP) had a lower Tg than that of stearic acid polyester (SAP), where PAP had a Tg of 1.8 °C, while SAP had a Tg of 31.9 °C. TGA demonstrated that thermal decomposition of both polyesters took place via two-stage processes, which occurred above 200 °C. GPC analysis showed that PAP (1031 g/mol) had a higher Mn value than SAP (972 g/mol). MTT assays were performed to determine the cytotoxicity of these polyesters against human keratinocytes (HaCaT), mouse fibroblasts (3T3), mouse hepatocytes (H2.35), and canine kidney cells (MDCK) in both dose- and time-dependent manners, with SDS serving as the experimental benchmark. Comparative cytotoxicity test showed that both PAP and SAP were biocompatibility and non-cytotoxic with the cell viability well above 80%, except SAP demonstrated a moderately low cytotoxicity on fibroblasts with cell viability remaining as 50.4% following 72 h exposure at 100 μg/mL of concentration. These findings suggest that the natural-sourced palm fatty acid polyesters have high potential to be used in pharmaceutical and nutraceutical applications.